Growth, plant height, physiological and quality of rockmelon (Cucumis melo L.) influenced by fertilizer types and pollinated bees (Trigona thoracica smith) under netted house - Nik Hassan, Nik Zuraila (2020)
Fertilizer is an important substance containing chemical element that improve rockmelon growth either from organic or inorganic source. To produce a good quality of rockmelon, it has to be planted in netted greenhouse to avoid pest and disease infection and irrigated using a fertigation system. However, farmers required high cost for greenhouse construction, fertilizer and labour to do assisted pollination for rockmelon production. Two experiments were carried out with the objectives of study were (i) to determine the changes on growth, yield and quality of rockmelon influenced by different types of fertilizer and (ii) to compare the successful rate of different pollination methods. The experiment was conducted in Field 2, Faculty of Agriculture, Universiti Putra Malaysia, Serdang, Selangor. In Experiment 1, five different ratio of organic (OF) and chemical (CF) fertilizer: (T1) 100% CF + 0% CF (1:0) as control, (T2) 75% CF + 25% OF (3:1), (T3) 50% CF + 50% OF (1:1), (T4) 25% CF + 75% OF (1:3) and (T5) 0% CF + 100% OF (0:1) were tested. The experiment was arranged in Randomized Complete Block Design (RCBD) with four replications. Plant height, leaf length and leaf width of rockmelon were measured at every week interval until 6 weeks after planting (WAP) of maximum growth, while physiological changes including photosynthesis, transpiration, stomatal conductance and chlorophyll content were measured at 30 and 60 days after planting (DAP). Rockmelon fruit diameter was measured at every week interval after flower bloomed. Fruit weight and postharvest quality rockmelon including soluble solid concentration (SSC), colour, firmness, sugar (sucrose, glucose and fructose) and organic acid (citric, malic, oxalic and succinic acid) as well as macronutrient content (N, P, K, Ca and Mg) in leaf tissue were measured at harvest stage. Plant height of rockmelon of T1 and T2 were significantly higher than T3, T4 and T5. The leaf length and width of rockmelon increased as plant height increased. The types of fertilizer used which has different composition of nutrient content has influenced on plant growth. Stomatal conductance, photosynthesis rate and transpiration rate on leaf also increased as plant height, leaf length and leaf width increases. Besides, stomatal conductance, photosynthesis rate and transpiration rate were higher at 30 DAP and decreased at 60 DAP. T1 had significant higher stomatal conductance, photosynthesis rate and transpiration rate compared to other treatment. The chlorophyll content of T5 and T1 increased at 30 DAP and the reading was decreasing for T1 at 60 DAP. T1 of rockmelon showed the highest fruit diameter and fruit weight followed by T2, T3, T4 and T5. The fruit colour in term of lightness (L*) and chromaticity (Ch*) had no significant difference among treatments, while hue angle (h*) of fruit is significant higher at T1 followed by T2 to T5 with no significant difference each other and T5 has the lowest Ch*. In addition, T1 showed the significantly highest SSC (14.5%) and lowest fruit firmness than other treatment followed by T2. The fruit firmness decreases as a result of SSC increases. There were significantly different on organic acid content between the treatments. Plant treated with T5 has the highest organic acid (oxalic, malic, citric and succinic acid). The amount of fumaric acid showed a little amount and almost closed each other between all treatments. In Experiment. 2, the effect of two factors including fertilizer type (FT) and pollination method (PM) were tested on growth and yield of rockmelon. The rockmelon plant was fertilized using different FT (T1 and T2) and were subjected to three PMs (bees, human and natural). The experiment was arranged in split plot design with factorial and four replications. Plant growth of each treatment showed no significant between treatment and no interaction between PM and FT. There were significantly different on pollination rate as influenced by PM, FT and interaction between PM and FT. Results showed rockmelon plant fertilized with T2 and pollinated by human showed the highest pollination rate compared to other treatment and followed by pollinated by bees under both types of fertilizer used. There were no significant difference on fruit weight, fruit diameter between treatments with T2 exhibited the highest fruit diameter than T1. The fruit SCC and firmness had significant interaction between PM and FT. Plant fertilized with T2 had the highest SCC and firmness than T1 treatment. There were no significant differences on organic acid of rockmelon between treatments. Significant interaction was found between PM and FT on sucrose content of rockmelon fruit. Rockmelon plant pollinated by bees had the highest sucrose content than human and natural pollination. Interestingly, rockmelon plant pollinated by bee was found successfully to increase number of fruit and number of survival bees is highest in netted greenhouse treated with T2 compared to netted greenhouse treated with T1. However, the number of dead bees increases with day after placing. In conclusion, T2 improved fruit quality and give the same yield as T1 besides reducing the amount of CF. The use of OF attract the bees to pollinate the flower than the use of CF with no different on organic compound of rockmelon fruit.